Dilatation of the ascending aorta in paediatric patients with bicuspid aortic valve: frequency, rate of progression and risk factors. Issue 10 (17th March 2006) - Warren, A E; Boyd, M L; O'Connell, C; Dodds, L
Abstract : Objectives: To describe the incidence and rate of dilatation of the ascending aorta in children with bicuspid aortic valve (BAV) and to determine factors that predict rapid aortic dilatation. Design: Retrospective cohort study. Setting: Regional tertiary care children's hospital. Patients: All children aged 0–18 years seen at the authors' institution between 1990 and 2003 with an "isolated" BAV. All patients had had more than one technically adequate echocardiogram, at least six months apart, with concomitant height and weight data. Interventions: Offline echocardiographic measurements of multiple levels of the aortic root were completed for each participant at each serial echocardiogram. These measurements were then compared with expected measurements derived from a normal local control population. Main outcome measures: Rate of change of the ascending aorta size over time, where aortic size is expressed as the number of standard deviations above or below the mean size expected for a given body surface area (z score). Results: 279 echocardiograms spanning a period of from 9 months to 13.3 years were analysed for 88 patients with BAV. The ascending aorta in the BAV group was larger than expected for body surface area at diagnosis and continued to increase in relative size at each of the four subsequent follow-up echocardiograms. Ascending aortic z score increased at an average rate of 0.4/year. A faster rate of increase in z score was predicted by both larger initial aortic valve gradient and non-use of β blockers. Conclusions: Children with BAV are at risk of having a dilated ascending aorta. This risk increases with longer follow up.